學童估測長度、面積與體積的表現與策略使用之探討 Investigation of the Performance and Use of Strategy Among Elementary School Children in Estimating Measurements of Length, Area, and Volume - 黃幸美 Hsin-Mei E. Huang (National Taiwan Normal University, 2016)
本研究發展一套估測評量以檢測學童在長度、面積與體積的估測能力與策略使用情形。研究對象為臺北市及新北市國小五～六年級學童948 位。研究結果發現：學童的估測表現與使用策略的數量，皆受年級與測量性質影響；87%以上的學童能使用策略估測，尤以身體部位與方便使用的物件為單位做估測的人次較高。整體而言，六年級學童的估測表現優於五年級，學童在不同的估測分測驗的表現亦呈現差異，他們在估測長度的表現優於估測面積與體積的表現。此外，使用於估測體積的策略數量高於估測面積與長度的策略數量，使用於估測面積的策略數量高於估測長度的數量；但策略數量的年級差異只呈現在面積估測問題；六年級學童的策略數量也高於五年級。 A set of measurement estimation assessments was developed to investigate the ability of elementary school children to estimate length, area, and volume measurements and their use of strategy in this context. The participants were 948 fifth- and sixth-graders who were recruited from elementary schools in Taipei and New Taipei City, Taiwan. The results showed that grade level and measurement attributes significantly influenced estimation performance and the number of strategies used in estimation. More than 87% of the children could indicate a strategy for estimating measurements. They frequently used body parts or objects that are convenient measurement units. On average, the sixth-graders outperformed the fifth-graders on the measurement estimation assessment. The students demonstrated higher performance in the subscale of length estimation than in the subscales of area and volume estimation. Multiple strategies were more commonly used for estimating volume than for estimating area and length. Participants also used a wider variety of strategies for estimating area than for estimating length. The influence of grade level on the degree of estimation strategy was observed only in the case of area estimation. Furthermore, the sixth-graders used more estimation strategies than the fifth-graders did.